2013
DOI: 10.1128/aac.00541-13
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M-123, a Novel Hybrid of the CTX-M-1 and CTX-M-9 Group β-Lactamases Recovered from Escherichia coli Isolates in China

Abstract: T he rapid and extensive dissemination of CTX-M-type extended-spectrum ␤-lactamases (ESBLs) in humans, animals, and the environment is one of the most successful stories of microbial drug resistance (1). CTX-M ␤-lactamases were originally named for their substrate preference for cefotaxime over ceftazidime (2), but subsequent microevolution means that many of the 140 variants currently listed (as of June 2013) at http://www.lahey.org /studies/other.asp#table1 confer resistance to both cefotaxime and ceftazidim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 19 publications
(22 reference statements)
10
28
1
Order By: Relevance
“…This suggests that recombination may take place between bla CTX-M- 14 and bla CTX-M-55 , producing various hybrid enzymes. Interestingly, all three published hybrids, CTX-M-64, CTX-M-123, and CTX-M-137, confer relatively high ceftazidime MICs compared to the majority of other CTX-M-type ESBLs (3)(4)(5). Conversely, the hydrolytic activities of CTX-M-55, CTX-M-123, and CTX-M-132 enzymes have not been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that recombination may take place between bla CTX-M- 14 and bla CTX-M-55 , producing various hybrid enzymes. Interestingly, all three published hybrids, CTX-M-64, CTX-M-123, and CTX-M-137, confer relatively high ceftazidime MICs compared to the majority of other CTX-M-type ESBLs (3)(4)(5). Conversely, the hydrolytic activities of CTX-M-55, CTX-M-123, and CTX-M-132 enzymes have not been described.…”
mentioning
confidence: 99%
“…More than 95% identity is often observed within the same cluster, whereas less than 90% identity is detectable between clusters (2). Several hybrids of the CTX-M-1 and -9 groups, namely, CTX-M-64, CTX-M-123, CTX-M-137, and CTX-M-132, have also been identified recently (3)(4)(5). Formation of these hybrid CTX-M enzymes was suggested to be the result of recombination between bla CTX-M- 15 and bla CTX-M-14 , the two most dominant variants detectable worldwide (1,6).…”
mentioning
confidence: 99%
“…CTX-M-137 is a simple hybrid, with the N terminus matching CTX-M-14 and the C terminus matching CTX-M-15 (6). The other three hybrids match CTX-M-1 group enzymes at the start and end but CTX-M-9 group enzymes in the middle, suggesting different double crossover events (4). Interestingly, these four CTX-M hybrids have all been found in China, where three of them were first reported, and have been detected in animals and in animal food (4,(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Four CTX-M enzymes (CTX-M-64, CTX-M-123, CTX-M-132, and CTX-M-137) that are hybrids of members of the CTX-M-1 and CTX-M-9 groups have emerged in recent years (4)(5)(6). CTX-M-137 is a simple hybrid, with the N terminus matching CTX-M-14 and the C terminus matching CTX-M-15 (6).…”
mentioning
confidence: 99%
“…The blaCTX-M-3 gene was frequently detected in Chinese hospitals [30,35]. The blaCTX-M-123 gene, a hybrid of blaCTX-M-1 and blaCTX-M-9 group genes, was first isolated from diseased animals in Guangdong province of China in 2010 [36]. SHV-12 was first reported in China, while a subsequent largescale study of isolates from six provinces, collected between 1998 and 2002, reported SHV-12 as the most common SHV type (ten isolates), with much smaller number of SHV-5, -2 and -9 [28].…”
Section: Discussionmentioning
confidence: 99%